Efficacy of Urinary Diversion in Gynecological Cases: A Retrospective Study at a Tertiary Referral Hospital - Rizza Maulana Azmi; Yufi Aulia Azmi; Brahmana Askandar Tjokroprawiro; Deepak Kumar Yadav; Ajit Khadga (Biomolecular and Health Science Journal)
Introduction: Gynecological malignancies are one of the most common cancers in women. Morbidity, in this case, can occur in patients with advanced cancer, and one of the causes is hydronephrosis. In the development of this case, a double-J stent (DJS) is usually used to treat urinary diversion. This research aimed to analyze the comparison of hydronephrosis patients from gynecologic oncology treated with DJS and without DJS. Methods: Retrospective research was conducted by reviewing 115 medical record data. Patients with hydronephrosis related to gynecologic oncology at a referral hospital in Surabaya, Indonesia, from January to August 2023 were included in this study. Data were analyzed using the Chi-square test for categorical data. For numerical data, they were analyzed using the Mann–Whitney test. Results: Cervical cancer was found in almost half of the total patients. Most patients undergo a DJS procedure. Nearly half of the patients experienced moderate category hydronephrosis before treatment and mild category after treatment. More than half of patients experience hydronephrosis on one side. The statistical test results of patients who underwent DJS installation and those who were not installed with DJS regarding the length of treatment (length of stay), prediversion creatinine, postdiversion creatinine, cancer stage, side of hydronephrosis, and length of operation showed P < 0.05. Conclusions: The use of urinary diversion in cases of gynecological malignancies can support the management of hydronephrosis in gynecological cancer patients. There are differences between patients who undergo DJS installation and those who do not undergo DJS installation, which show specific indications.